Aβ inhibits mesenchymal stem cell–pericyte transition through MAPK pathway. (23rd June 2018) - Xu, Lixia; Li, Jialin; Luo, Zhongqiu; Wu, Qiaoli; Fan, Weijia; Yao, Xiuhua; Li, Qingguo; Yan, Hua; Wang, Jinhuan
Abstract: Multiple independent reports have demonstrated pericyte loss in both the hippocampus and cortex in human Alzheimer's disease (AD). The differentiation and recruitment of pericytes are the essential steps in vasculature development. However, the role of amyloid beta (Aβ) in pericyte differentiation has not yet been fully elucidated. In this study, we investigated the interaction between Aβ and differentiation of mesenchymal stem cells (MSCs) toward pericytes in culture. Our results showed that mice overexpressing Aβ-precursor protein (APP/PS1) exhibited the loss of pericytes compared with the control group mice, evidenced by the lack of desmin expression in the cortex of 12-month-old mice. Interestingly, we further found that both Aβ40 and Aβ42 inhibited the expressions of pericyte markers (α-SMA, desmin, and PDGFRβ) in cultured MSCs which can be differentiated into mature pericytes. Mechanistically, the inhibitory effects of Aβs on MSC–pericyte transition is mediated by the activation of the ERK1/2 MAPK signal pathway. These new insights into the roles of Aβ in pericyte differentiation may help to develop more effective strategies for the treatment of AD.